The Impact of the Immune System on Tumor: Angiogenesis and Vascular Remodeling - Stockmann, Christian; Schadendorf, Dirk; Klose, Ralph; Helfrich, Iris (Frontiers in Oncology, 2014)
Angiogenesis, the formation of new blood vessels, as well as inflammation with massive infiltration of leukocytes are hallmarks of various tumor entities. Various epidemiological, clinical, and experimental studies have not only demonstrated a link between chronic inflammation and cancer onset but also shown that immune cells from the bone marrow such as tumor-infiltrating macrophages significantly influence tumor progression. Tumor angiogenesis is critical for tumor development as tumors have to establish a blood supply in order to progress. Although tumor cells were first believed to fuel tumor angiogenesis, numerous studies have shown that the tumor microenvironment and infiltrating immune cell subsets are important for regulating the process of tumor angiogenesis. These infiltrates involve the adaptive immune system including several types of lymphocytes as well as cells of the innate immunity such as macrophages, neutrophils, eosinophils, mast cells, dendritic cells, and natural killer cells. Besides their known immune function, these cells are now recognized for their crucial role in regulating the formation and the remodeling of blood vessels in the tumor. In this review, we will discuss for each cell type the mechanisms that regulate the vascular phenotype and its impact on tumor growth and metastasis.